A study on Hydrochemical characteristics of Surface and Sub-surface water in and around Perumal Lake, Cuddalore District, Tamilnadu, South India. - Prasanna, Mohan Viswanathan; Chidambaram, S.; Gireesh, T.; Jabir ali, T. (Springer-Verlag, 2010)
Hydrogeochemical investigations are carried out in and around Perumal Lake, Cuddalore district, SouthIndia in order to assess its suitability in relation to domestic and agricultural uses. The water samples (surface water = 16; groundwater = 12) were analyzed for various physicochemical attributes like pH, electrical conductivity (EC), sodium (Na+), potassium (K+), calcium (Ca2+), imagnesium (Mg2+), chloride (Cl-), bicarbonate (HCO3-), sulfate (SO42-), phosphate (PO4), silica (H4SiO4) and totaldissolved solids (TDS). Major hydrochemical facies were identified using Piper trilinear diagram. Hydrogeochemical processes controlling the water chemistry are water-rock interaction rather than evaporation and precipitation. Interpretation of isotopic signatures reveals that groundwater samples recharged by meteoric water with few water-rock interactions. A comparison of water quality inrelation to drinking water quality standard proves that the surface water samples are suitable for drinking purpose, whereas groundwater in some areas exceeds the permissible limit. Various determinants such as sodium absorption ratio (SAR), percent sodium (Na%), residual sodium carbonate (RSC) and permeability index (PI) revealed that most of the samples are suitable for irrigation.